Genetics of Alzheimer Disease - Rao, A.T.; Degnan, A.J.; Levy, L.M. (American Journal of Neuroradiology, 2014)
SUMMARY: Alzheimer disease prevails as a major cause of disability in the elderly population and ranks as the most common form of dementia that affects 1 of 8 individuals older than 65 years of age. Most AD cases are late in onset and are probably influenced by both genetic and environmental factors. Apart from age, the risk factors include family history; brain injury, both traumatic and vascular; and metabolic diseases, such as diabetes, hypercholesterolemia, and obesity. Based on twin studies, inheritance plays a role in approximately 80% of cases (familial and sporadic). ADAlzheimer diseaseAPPamyloid protein precursorPENS1presenilin 1PENS2presenilin 2Aβamyloid-βAPOEapolipoprotein E